2017
DOI: 10.1038/s41598-017-17906-w
|View full text |Cite
|
Sign up to set email alerts
|

High Energy Density in Azobenzene-based Materials for Photo-Thermal Batteries via Controlled Polymer Architecture and Polymer-Solvent Interactions

Abstract: Energy densities of ~510 J/g (max: 698 J/g) have been achieved in azobenzene-based syndiotactic-rich poly(methacrylate) polymers. The processing solvent and polymer-solvent interactions are important to achieve morphologically optimal structures for high-energy density materials. This work shows that morphological changes of solid-state syndiotactic polymers, driven by different solvent processings play an important role in controlling the activation energy of Z-E isomerization as well as the shape of the DSC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…87 This concept has also been successfully used to form AZO-based polymers with energy densities up to 0.7 MJ kg À1 . 88 Furthermore, it is also possible to incorporate two or more photoswitches into macrocyclic structures where the macrocycle strain may influence the energetics of the system as well. One example of this is cyclic systems with multiple AZO units, where both storage energy and storage time are augmented because of the cyclic arrangement (Figure 5).…”
Section: Ll Open Accessmentioning
confidence: 99%
“…87 This concept has also been successfully used to form AZO-based polymers with energy densities up to 0.7 MJ kg À1 . 88 Furthermore, it is also possible to incorporate two or more photoswitches into macrocyclic structures where the macrocycle strain may influence the energetics of the system as well. One example of this is cyclic systems with multiple AZO units, where both storage energy and storage time are augmented because of the cyclic arrangement (Figure 5).…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Among the photoswitching molecular systems listed, azobenzene derivatives have been particularly well explored as MOST compounds due to a plethora of functionalization methods , available and their remarkable E–Z isomerization cyclability . Various forms of MOST materials have been developed incorporating azobenzene groups, including small molecules, , oligomers, , polymers, , carbon nanotubes, , and graphene oxides, , and have demonstrated energy storage in the metastable Z isomer state upon UV irradiation. One challenge that azobenzene derivatives face as MOST storage materials is their short Z isomer half-life ( t 1/2 ), ranging from seconds to days depending on azobenzene functionalization. , The thermal stability of the Z isomer is determined by both steric and electronic effects on both the E/Z ground states and isomerization transition state. , Such thermal stability governs the thermal energy storage lifetime in MOST materials, and various molecular designs have been developed to increase thermal stability of azobenzene Z isomers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the selection of solvents can influence the T g of a polymer by altering the packing density and morphology of the polymer. 35 Moreover, it has been observed that the T g of a polymer film can change with film thickness and the type of substrate that the film is cast on. 36 Thus, it is possible that the lower value of the observed T g for the PMMA coating film is probably due to a combination of these reasons.…”
Section: Resultsmentioning
confidence: 99%